Investigation of asphalt concrete used as the ballastless track substructure in long-span railway bridges - Gang Liu; Zhendong Qian; Diyun Yang; Yang Liu; Yuxiang Yin (Case Studies in Construction Materials, 2022)
The application of asphalt concrete is common in railways. However, the asphalt concrete substructure (ACS) is mainly used above the subgrade of general railway. The studies on the asphalt concrete used as the ballastless track substructure in long-span railway bridges (LSRB) still remained to be explored. The purpose of this research is to clarify mechanical responses of the ballastless track ACS in LSRB, and determine its structure and material design method. Firstly, the numerical model of LSRB ballastless track model with the ACS was established. Then, the mechanical responses of ACS under the train load were obtained. Besides, the effects of temperature changes and substructure thickness on the mechanical responses were also discussed. Next, the recommended substructure thickness and material design indicators were given based on the simulation results and environment requirements. Lastly, a type of designed asphalt concrete was taken as a case study, and its material performance was evaluated based on the proposed design indicators. Results show that the temperature has a great effect on its mechanical response. Its thickness was recommended as 300 mm. The designed asphalt concrete can meet the proposed technical requirements. The findings in this paper could provide a reference to the design of the ballastless track ACS in LSRB.